The Global Hub Process: Malaysia’s Vision towards Becoming the Islamic Finance Global Hub Country - Mohd Nazri Mohd Noor; Mohammad Noorizzuddin Nooh; Joni Tamkin Bin Borhan (Center for Promoting Ideas (CPI), USA, 2024)
This study attempts to look upon a development process of global financial center and further, aims to analyze Malaysia’s vision in positioning the country as Islamic finance Global Hub. As the financial movement and development take a fast change, it is vital to understand on how the evolution of trade works and transforms from the national level into the international or global level. Malaysia is well-known as a country with an advance Islamic financial system. The government has set up a plan to position the country as Islamic finance global hub. Through this study, the understanding of global hub process will ensure that the vision runs under a proper manner and eventually put the vision into a success.